EMENDA AO GÊNERO FURARIUM RIZZ. (LORANTHACEAE) - Carlos Toledo Rizzini (Rodriguésia)
Summary The loranthaceous genus Furarium was formerly described (Rizzini, 1956) as devoid of bracteoles in the cavities of the rachis in viihich the flowers are inserted. Recent reexamination of an extremely favorable specimen has shown that such bracteoles do exist and are even well developed. Moreover, it was disclosed that the flowers are both unisexual and arranged In ternations. In view of these new features the generic and specific diagnoses have to be amended in certain details. As a result, Furarium has got intermediate between Phthirusa (by the ternations inside bracteolar cups and dieline flowers) and Oryctanthus (by the excavated inflorescence axes). It differs from both of them by its conspicuous, closely imbricate bracts toward the spike apex (hence strobiliform spikes) allied to the amply divergent anther thecae.